Mujeres malas. La representación del delito femenino en la prensa de principios del siglo XX - Rivera Aravena, Carla (Revista de Historia Social y de las Mentalidades, 2011)
The investigator analyses the construction of a specific imaginary of fem inine criminal subjects in the beginning of the twentieth century, in aneminently moderns upport: the press. Her work tries to uncover the mechanisms discovered in «the power of the journalistic di s course» to preserve status quo, controlling those who escape the norm through the creation of images that mark and re signify the social subjects th at break away from the esta blished order.
Keywords: Representation; Subordination; Women; Police chronicle